The Inhibin B Response to the Testicular Toxicant 1, 3 Dinitrobenzene in Male Rats. (24th January 2013) - Sonee, Manisha; Bogdan, Nancy; Hall, LeRoy; Bryant, Stewart; Vinken, Petra
<x xml:space="preserve">Abstract</x> BACKGROUND This study was conducted as part of an ILSI‐HESI International Life Sciences Institute‐Health & Environmental Sciences Institute consortium effort to assess the utility of circulating Inhibin B as an early biomarker of Sertoli cell‐specific testicular toxicity in rats. 1, 3‐Dinitrobenzene (1, 3‐DNB) was selected as a testicular toxicant in this study as it is known to target Sertoli cells. METHODS 1, 3‐DNB (2 and 6 mg/kg/day) or control (corn oil) was administered orally to male rats for two or five consecutive days. Blood was collected from rats treated for 2 days on days 1 and 2 and from rats treated for 5 days on days 1, 3, and 5. The resulting serum was evaluated for Inhibin B and follicle stimulating hormone. At the end of the treatment periods, the testes were removed, weighed, and examined histopathologically. RESULTS Daily administration of 1, 3‐DNB resulted in decreased testis weight only on day 5 and only at the high dose (6 mg/kg/day). There was a time‐dependent increase in incidence and severity of testicular findings characterized by degeneration of the germinal epithelium with loss of pachytene spermatocytes and vacuolization of the Sertoli cells in the seminiferous tubules at the high dose. Inhibin B levels in 1, 3‐DNB‐treated animals were decreased with treatment only on day 5 at the high dose; there were no associated changes in follicle stimulating hormone. CONCLUSIONS Changes in serum Inhibin B levels were detected only in association with moderate or severe testicular toxicity as evidenced by histopathology and is therefore considered to be of limited value as a biomarker for Sertoli cell toxicity.